Upaya Meningkatkan Hasil Belajar Ipa dengan Model Pembelajaran Scramble-Media Visual Peserta Didik Kelas IV SDN 4 Panarung Tahun Pelajaran 2017/2018: Effort Increasing Learning Results with Scramble-Visual Media Learning Model on Participants 4th Grade 4th Panarung Elementary School Lesson Year 2017/2018 - Yantol, Rahmi; Diplan, Diplan; Kartini, Nurul Hikmah (Jurnal Hadratul Madaniyah, 2018)
This study aims to: (1) describe the learning activities of grade 4 students of SDN 4 Panarung at the time of science teaching using Scramble-Visual media, (2) to know the learning outcomes of science students of grade IV SDN 4 Panarung by using the learning model Scramble-Visual media. The method and type of research used in this research is Classroom Action Research (PTK). The results showed that: (1) Students' learning activities in good category became better in science lesson using visual media assisted media scramble model in fourth grade of SDN 4 Panarung in academic year 2017/2018. Learners play an active role, motivated, cooperate with each other to improve the concentration and speed of thinking during the learning process in cycle I. The results of observers of teacher activity on the learning process conducted by observers I and observer II during the process of learning science (natural) the teacher activity is 3.61 with very good criteria and the average activity of learners is 3.55 with very good criteria. (2) There is an improvement of science learning outcomes of students of class IV in SDN 4 Panarung academic year 2017/2018 after using the model of learning scramble with visual media assisted. This shows the results of learning through the average score of the class on the initial test is 43 and the percentage of learning mastery learners classically 9.52% with the criteria not achieved. In the first cycle, the average score of the class is 70 and the percentage of students' learning completeness classically is 100%, from the predetermined criteria that is KKM is 65 and the criteria completeness 85% classically achieved category.